Carbonylative transformation of aryl halides and strong bonds via cheap metal catalysts and sustainable technologies - Maolin Yang; Yukun Liu; Xin Qi; Yanhua Zhao; Xiao-Feng Wu (Green Synthesis and Catalysis)
The development of catalytic carbonylation reactions has increased considerably. Although many reviews/chapters/books on carbonylation reactions have been published, summaries on cheap metal-catalyzed catalytic carbonylation reactions of aryl halides and other chemical bonds with high dissociation energy C–Y (Y ​= ​O, N, H) are still very rare. Focusing on green and sustainable chemistry, this review summarizes and discusses the achievements on carbonylative transformations of aryl halides (C(sp2)–X) and strong bonds C–Y (Y ​= ​O, N, H) based on non-expensive metal catalysts (Co, Mn, Mo, Ni, Fe, Cu), photochemical and electrochemical systems developed in recent decades.